REORIENTASI PERAN POLRI DALAM PENANGANAN KONFLIK SOSIAL DARI PERSPEKTIF PENEGAKAN HUKUM - Arjun Rojalio Hibrizi; Alphany Dyah Eka Putri, Annisa Frizki Maharani, Keyzia Zachwa Rachmadhina, Tugimin Supriyadi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Effective handling of social conflicts requires a holistic and humanist approach, especially from law enforcement agencies such as the National Police. The reorientation of the National Police's role in handling social conflicts emphasizes fair, transparent and accountable law enforcement. This research highlights the importance of the National Police adopting preventive and proactive strategies to detect and prevent conflict early through partnerships with the community and related organizations. A humanist law enforcement approach that respects human rights is also a main focus, with the aim of not only overcoming conflict but also providing long-term solutions. Apart from that, increasing the capacity and competence of Polri personnel through continuous training is very necessary so that they are better prepared and professional in dealing with conflict situations. Strong collaboration between government agencies and non-government institutions as well as the use of advanced information technology were also identified as key factors in increasing the effectiveness of handling social conflicts by the National Police. With the right reorientation, the National Police can play a more effective role in maintaining security, public order, and supporting the creation of peace and social justice in Indonesia. Reorientation of the role of POLRI must be carried out immediately in resolving conflicts. Another goal is to understand strategies and mechanisms for handling social conflict to achieve peace in line with legal demands, democratization, justice and truth, and human rights. The research results found that in handling social conflict, POLRI as law enforcers tasked with maintaining domestic security are required to have professional and proportional expertise and skills that are in line with legal demands, democratization, justice and truth, as well as human rights.